Analysis of the Effect of Service Quality and Digital Saving on Customer Statisfaction at Bank BCA Prima Sunter Brnch - Yesika Tarigan; Rakhmat; Reni Yesi (Mulia Pratama, 2024)
The author aims to explain whether the variables of service quality and digital savings have a significant effect on customer satisfaction at PT. BCA This type of research uses primary data collection methods, namely field research which is carried out by direct observation (observation), interviews and using a list of questions (questionnaires). The sample method used is a saturated sampling technique, namely: a total of 60 respondents The analysis data was carried out using multiple linear regression analysis methods, dermination coefficient analysis, t test, f test in the SPPS program version 26. Based on the calculation of the coefficient analysis of determination (R2) of the SPSS program is 0.482, the correlation analysis of determination R2 obtained the value of Kd = ( 0.577 x 0.577 = 0.333 ) 33.3% and the remaining 100% - 33.3% = 66.7% influenced by other variables Based on the partial test results of service quality t calculate 3.690 >2.001 t table with a significant value of 0.01 because the significant probability is much smaller than 0.05 then HO is rejected and Ha is accepted. This shows that it partially states that the quality of service . Based on the hypothesis test f obtained a value of 14.228 with df numerator 2 and df denominator 58 then obtained f table of 3.16 because f count 14.228 > table 3.16, then HO is rejected and Ha is accepted meaning that there is a significant influence between service quality (X1) and digital savings (X2) together on the variable digital savings (Y) at PT BCA. There is a significant influence between service quality (X1) and work digital savings (X2) together on the customer statisfactions variabel (Y) at Bank BCA Prima Sunter Branch